Impact of ocean warming and ocean acidification on larval development and calcification in the sea urchin Tripneustes gratilla. - Hannah Sheppard Brennand (Public Library of Science (PLoS), 2010)
Background As the oceans simultaneously warm, acidify and increase in P(CO2), prospects for marine biota are of concern. Calcifying species may find it difficult to produce their skeleton because ocean acidification decreases calcium carbonate saturation and accompanying hypercapnia suppresses metabolism. However, this may be buffered by enhanced growth and metabolism due to warming. Methodology/principal findings We examined the interactive effects of near-future ocean warming and increased acidification/P(CO2) on larval development in the tropical sea urchin Tripneustes gratilla. Larvae were reared in multifactorial experiments in flow-through conditions in all combinations of three temperature and three pH/P(CO2) treatments. Experiments were placed in the setting of projected near future conditions for SE Australia, a global change hot spot. Increased acidity/P(CO2) and decreased carbonate mineral saturation significantly reduced larval growth resulting in decreased skeletal length. Increased temperature (+3 degrees C) stimulated growth, producing significantly bigger larvae across all pH/P(CO2) treatments up to a thermal threshold (+6 degrees C). Increased acidity (-0.3-0.5 pH units) and hypercapnia significantly reduced larval calcification. A +3 degrees C warming diminished the negative effects of acidification and hypercapnia on larval growth. Conclusions and significance This study of the effects of ocean warming and CO(2) driven acidification on development and calcification of marine invertebrate larvae reared in experimental conditions from the outset of development (fertilization) shows the positive and negative effects of these stressors. In simultaneous exposure to stressors the dwarfing effects of acidification were dominant. Reduction in size of sea urchin larvae in a high P(CO2) ocean would likely impair their performance with negative consequent effects for benthic adult populations.